X, T-phase diagram of PbFe1/2Ta1/2O3-PbTiO3 solid solution. Issue 1 (19th May 2021) - Raevskaya, S. I.; Malitskaya, M. A.; Sitalo, E. I.; Raevski, I. P.; Lutokhin, A. G.; Zakharov, Y. N.; Titov, V. V.; Zakharchenko, I. N.; Chou, C.-C.
Abstract: x, T -phase diagram of the solid solution of multiferroic PbFe1/2 Ta1/2 O3 with ferroelectric PbTiO3 for the 0 ≤ x ≤ 0.3 compositional range was plotted for the first time using the data of dielectric, piezoelectric, and Mössbauer studies.